Interpreter training for medical students: pilot implementation and assessment in a student-run clinic. Issue 1 (December 2016) - Diaz, Jennifer; Ekasumara, Nydia; Menon, Nikhil; Homan, Edwin; Rajarajan, Prashanth; Zamudio, Andrés; Kim, Annie; Gruener, Jason; Poliandro, Edward; Thomas, David; Meah, Yasmin; Soriano, Rainier
Abstract Background Trained medical interpreters are instrumental to patient satisfaction and quality of care. They are especially important in student-run clinics, where many patients have limited English proficiency. Because student-run clinics have ties to their medical schools, they have access to bilingual students who may volunteer to interpret, but are not necessarily formally trained. Methods To study the feasibility and efficacy of leveraging medical student volunteers to improve interpretation services, we performed a pilot study at the student-run clinic at the Icahn School of Medicine at Mount Sinai. In each fall semester in 2012–2015, we implemented a 6-h course providing didactic and interactive training on medical Spanish interpreting techniques and language skills to bilingual students. We then assessed the impact of the course on interpreter abilities. Results Participants' comfort levels, understanding of their roles, and understanding of terminology significantly increased after the course (p < 0.05), and these gains remained several months later (p < 0.05) and were repeated in an independent cohort. Patients and student clinicians also rated participants highly (averages above 4.5 out of 5) on these measures in real clinical encounters. Conclusions These findings suggest that a formal interpreter training course tailored for medical students in the setting of a student-run clinic is feasible and effective. This program for training qualified student interpreters can serve as a model for other settings where medical students serve as interpreters.